Urban Transition Toward Environmental Sustainability: Instrumentation and Institutionalization of Co‐Creation - Ben Vermeulen; Lennart Winkeler; Mohar Kalra (Urban Planning, 2025)
The transition in cities toward environmental sustainability requires transforming urban subsystems such as energy, transport, and waste infrastructure. Based on the frameworks of strategic spatial planning (SSP) and urban transition management (UTM), the urban transition is conceptualized as a long‐term process in which stakeholders co‐create a vision and a strategic plan, which is subsequently implemented in multiple relatively short‐term projects transforming these urban subsystems. While co‐creation is emerging in urban planning, ambiguity remains regarding the development and use of co‐creation instruments in transforming urban subsystems. This article therefore has two aims: first, to develop a typology of co‐creation instruments for urban transition planning and management; and second, to examine the institutionalization of their development and use. The article follows an iterative inductive‐deductive search method to make an inventory of instruments, after which four main types are identified: participatory planning and communication tools, expert planning support systems, urban living labs, and virtual transformation labs. Several challenges in using these instruments are identified, including the need to acquire governance and digital skills, and to keep tools and data up to date. This article subsequently examines the capabilities that need to be institutionalized to support the use and development of these instruments across multiple projects. Capabilities needed are stakeholder engagement and collaborative governance, the participatory design and updating of digital tools, maintenance of urban subsystem and city development models, definition of transition scenarios and experiments, and interpretation of (simulation) results. Additional capabilities are needed to manage the project portfolio and facilitate learning within and across projects. Ultimately, a “Transition Planning Office” is proposed to institutionalize these capabilities and, by doing so, to complement UTM’s focus on independent vision and agenda formulation with sustained involvement in long‐term planning, and to support SSP’s call for more strategic urban planning through project portfolio management and instrument use and development.